Revisiting “USP for All?”: Permanent challenges in the inclusion of low-income students in Brazilian public higher education. - Almeida, Wilson Mesquita de (Revista de Ciências Sociais, 2020)
The article takes up the context, problems and theoretical and methodological challenges of the qualitative empirical research that culminated in the book “USP para Todos?”, From a dialogue with changes that have occurred since then in the access and permanence of low-income students and those coming from school public in Brazilian higher education - especially, public. In doing so, it discusses elements that we still consider relevant for critical reflection in this field of knowledge.